Cardiovascular benefits of a home-based exercise program in patients with sickle celldisease - Junior, Jonas Alves Araujo [UNESP]; Rossi, Daniele Andreza Antonelli [UNESP]; Valadao, Taina Fabri Carneiro [UNESP]; Mattos, Juliana Cristina Milan; Catai, Aparecida Maria; Sato, Tatiana De Oliveira; Hueb, Joao Carlos [UNESP]; Bazan, Silmeia Garcia Zanati [UNESP]; Hokama, Paula Oliveira Montandon [UNESP]; Hokama, Newton Key [UNESP]; Roscani, Meliza Goi [UNESP] (Public Library of Science (PLoS), 2021)
Background Physical inactivity is an important risk factor for cardiovascular disease. The benefits of exercise in patients with chronic diseases, including cardiovascular diseases, are well established. For patients with sickle cell disease, medical recommendation was to avoid physical exercise for fear of triggering painful crises or increasing the impairment of the cardiopulmonary function. Only recently, studies have shown safety in exercise programs for this population. Despite that, there is no report that assess the effects of physical exercise on cardiac parameters in patients with sickle cell disease. Objective This study aimed to evaluate the impact of regular physical exercise (a home-based program) on cardiovascular function in patients with sickle cell disease. Design A quasi-randomized prospective controlled trial. Setting During the years 2015 and 2016, we started recruiting among adult patients treated at a Brazilian Center for Patients with Sickle Cell Disease to participate in a study involving a home exercise program. The experimental (exercise) and control groups were submitted to clinical evaluation and cardiovascular tests before and after the intervention. Analysis of variance was applied to compare groups, considering time and group factors. Participants Twenty-seven adult outpatients with a sickle cell disease diagnosis. Interventions Exercise group (N = 14): A regular home-based aerobic exercise program, three to five times per week not exceeding give times per week, for eight weeks; no prescription for the control group (N = 13). Main outcome measures Echocardiographic and treadmill test parameters. Results The exercise group showed significant improvement in cardiovascular tests, demonstrated by increased distance traveled on a treadmill (p0.01), increased ejection fraction (p 0.01) and improvement of diastolic function assessed by mitral tissue Doppler E wave on echocardiography (p = 0.04). None of the patients presented a sickle cell crisis or worsening of symptoms during the exercise program. Conclusion The selected home-based exercise program is safe, feasible, and promotes a favorable impact on functional capacity and cardiovascular function in sickle cell disease patients.